Determinants Of Non-Revenue Water In Urban Water Supply: The Case Of Adama City, Ethiopia - Muktar Kasso (ASTU, 2023)
The Water Loss Problem Is A Challenge For Water Utilities In Providing A Satisfactory Water Supply To The Rapidly Growing Population Of Urban Settlements. A Significant Amount Of Water Is Lost In The Form Of Non-Revenue Water (Nrw) Annually. The Global Volume Of Nrw Has Been Estimated To Be 126 Billion Cubic Meters Per Year. In Africa, Nrw Figures Ranging From 5% (Saldanha Bay, South Africa) To 70% (Lwsc,Liberia) Have Been Reported. In The Urban Water Supply Of Ethiopia, Only 45% Of The Urban Ethiopian Population Has Been Using Water From Safely Managed Water Services In 2020. The Water Losses Of Adama City Were As High As 34.67 % To 34.05 % As Per Earlier Literature. The Overall Objective Of This Study Was To Investigate Determinants Of Non-Revenue Water (Nrw) In Adama City??S Water Supply System. The Study Used Primary Data And Secondary Data. A Pre-Determined Information-Oriented Target Population Of A Total Of 35 Members Of The Staff Of The Adama Water Supply And Sewerage Service Enterprise (Wssse) Was Considered For The Study. International Water Association (Iwa) Water Balance Through American Water Works Association (Awwa) Water Audit Software Is Used For Analysis. The Level Of Non-Revenue Water In The 2014 Ethiopian Fiscal Year (Efy) Was As High As 20% Of The Total System Input Water Volume In The Case Of Continuous 24 Hours Supply System While It Is 40% In Intermittent Supply Of Average 12 Hours Run Time. It Is Higher Than The Acceptable 15% Nrw Percentage Set By The Federal Democratic Republic Of Ethiopia (Fdre), Ministry Of Water,Irrigation And Energy (Mowie) Design Criteria. The Findings Of The Study From Respondents Show That The Key Factors Influencing Nrw Of The City Water Supply System Are Real Losses (Pipe Bursts And Leakages) Followed By Unauthorized Consumption (Illegal Connections). The Study Also Showed That Meter Registration Errors (Inaccuracy) And Unbilled Unmetered Consumption Are Additional Factors Contributing To The Nrw Consecutively. From Awwa Water Audit Software Similar Outputs Were Observed Indicating High Pipe Bursts And Leakages Followed By Apparent Losses And Unbilled Unmetered Consumption. To Reduce The Nrw Levels Of The City, The Management Of Adama Wssse And Concerned Body Should Develop And Implement An Nrw Reduction Strategy At The Adama Water Supply Scheme That Should Include Reduction Of Water Lost Through Bursts And Leakages, Reduction Of Unauthorized Consumption (Illegal Connections), Meter Registration Accuracy Enhancement And Reduction Of Unbilled Unmetered Consumption.
Keywords: Adama City, Non-Revenue Water (NRW), Water loss, Water Supply system